Electrode surface modification using iron(II) phthalocyanine immobilized via electrografting and click chemistry and clicked onto azide-functionalized quantum dots: applications in electrocatalysis - Nxele, Siphesihle Robin (Rhodes University, Faculty of Science, Department of Chemistry, 2016)
Tetrakis(5-hexynoxy)Fe(II) phthalocyanine was used alone and in combination with quantum dots (QDs) in order to test the electrocatalytic ability with hydrazine and paraquat as the analytes of interest. This novel phthalocaynine was successfully synthesised and characterized using various characterisation techniques. The QDs used were the well-known core-shell CdSe/ZnS nanostructures. The fabrication of glassy carbon electrodes involved covalent attachment by electrochemical grafting and click chemistry for the first part of the work and the second part involved the conjugation of the synthesised QDs and the phthalocyanine by click chemistry. This approach of conjugating these nanostructures introduced another aspect of novelty to the work reported in this thesis. The immobilisation of this conjugate on a glassy carbon electrode (GCE) was achieved by adsorption. Characterisation techniques such as infrared spectroscopy, x-ray diffractometry, UV/vis spectroscopy, transmission electron microscopy and x-ray photoelectron spectroscopy were used to characterise the molecules and conjugates of interest. With respect to the electrocatalytic part of the work, electrode surface characterisation involved scanning electrochemical microscopy and cyclic voltammetry to determine changes in the nature of the surface as well as reactivity of the surface at different modification steps. Detection limits and the sensitivity determined for the electrocatalysts fabricated here proved to be an improvement compared to other reported work involving phthalocyanines and the test analytes chosen for application. With respect to the conjugate, the electrocatalytic ability was improved when the QDs and phthalocyanine were combined using click chemistry compared to using the phthalocyanine alone.
Keywords: Uncatalogued